2007
DOI: 10.1007/s00198-007-0357-5
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in leukocytes correlates with bone mineral density and is shorter in women with osteoporosis

Abstract: Shortened leukocyte telomere length is independently associated with a decrease in BMD and the presence of osteoporosis in women. Our data provide evidence that leukocyte telomere length could be a marker of biological aging of bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
3
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 36 publications
6
108
3
4
Order By: Relevance
“…Table 1 lists demographic information for this control multiethnic group in comparison with subjects with pulmonary fibrosis. The rate of TRFL shortening in normal samples was 17 bp/year (Figure 2A), which is consistent with prior estimates that leukocyte telomere shorten by 15-40 bp/year within this age range (18)(19)(20)(21)(22). A small difference in mean TRFLs between the men (5.84 kb) and women (6.03 kb) was found (P 5 0.02), which is consistent with other studies (21,23).…”
Section: Comparison Of Telomere Lengths To Those Of a Normal Populationsupporting
confidence: 90%
See 1 more Smart Citation
“…Table 1 lists demographic information for this control multiethnic group in comparison with subjects with pulmonary fibrosis. The rate of TRFL shortening in normal samples was 17 bp/year (Figure 2A), which is consistent with prior estimates that leukocyte telomere shorten by 15-40 bp/year within this age range (18)(19)(20)(21)(22). A small difference in mean TRFLs between the men (5.84 kb) and women (6.03 kb) was found (P 5 0.02), which is consistent with other studies (21,23).…”
Section: Comparison Of Telomere Lengths To Those Of a Normal Populationsupporting
confidence: 90%
“…To minimize the size of subtelomeric sequences, we digested the genomic DNA with six different 4-bp restriction enzymes. We observed a comparable rate of telomere length attrition with age (17 bp/yr) in normal individuals of this age range, as have other investigators who have used this same method (18)(19)(20)(21)(22). The quantitative PCR measurement of telomere length offers an independent method for estimating telomere length from genomic DNA and we found a good correlation between these two methods.…”
Section: Table 3 Distribution Of Case Subects and Control Subjects Ssupporting
confidence: 88%
“…(49,50) Finally, bone mass showed small but significant correlation with telomere length. (51,52) In conclusion, our findings implicate telomere shortening in the pathogenesis of age-related bone loss owing to multiple cellular and molecular mechanisms (Fig. 6).…”
Section: Discussionmentioning
confidence: 53%
“…Some studies suggest that baseline TL is associated with late events of hematologic relapse in aplastic anemia patients treated with immunosuppressant therapy [60]. Valdes et al [61] showed that clinical osteoporosis is related to shorter telomeres in over 2000 women, in whom leukocyte telomere length was significantly correlated with bone mineral density. This result was corroborated by Tang et al [62], who analyzed women and men regarding telomere length and bone marrow density, and a positive correlation was found for females.…”
Section: Telomere Length and Human Healthmentioning
confidence: 99%